Keterkaitan Mahasiswa Praktek Klinik Keperawatan Jiwa Prestasi Belajar Dengan Tingkat Kecemasan - Sucipto Sucipto; Moh Alimansur (coba, 2014)
Environmental hospital clinic is the only source of greatest anxiety for the students of nursing (Triyana, 2002). The nursing students in the clinical practice of the hospital will experience difficulties in the beginning of practice, almost all students experience anxiety when beginning the practice (Sharif and Masoumi, 2005). Anxiety that occurs in the student will certainly affect the success of nursing clinical practice mental activity. This research is a descriptive cross sectional analytic approach. The study population is the entire third level students who will carry out the Clinical Practice Psychiatric Nursing. The sample in this study is partially third level students who will carry out the Clinical Practice Psychiatric Nursing Nursing Academy Dharma Husada Kediri academic year 2013/2014 with a sample size of 90 respondents. Statistical tests used in the study is the Spearman rho test. The results of the statistical test using the Spearman rho Spearman correlation values obtained at 0.238 with a p-value = 0.024. This result shows the p-value <o, o5 which means there is a relationship between anxiety students with student achievement in taking psychiatric nursing care Course II. Keyword: Anxiety, Student Achievement